THE Optimizing Learners' Development Through Ubrug Banten Learning with an Ethnopedagogy Approach - Andriana, Encep; Leksono, Suroso Mukti; Jamaludin, Ujang; Muhyidin, Asep (Jurnal Profesi Keguruan, 2024)
This study aims to examine how Ubrug Banten learning can optimize learners' development. Ubrug Banten is a cultural practice that originated and evolved within the community of Banten. The research adopts a descriptive qualitative methodology with an ethnographic approach. It seeks to illustrate the Ubrug Banten phenomenon and its potential contributions to education in Indonesia. The study employed interviews, observations, and documentation as data collection methods. The data were analyzed using reduction, presentation, and decision-making techniques. The findings indicate that Ubrug Banten aligns with the criteria of ethnopedagogy. Additionally, this cultural practice holds valuable lessons that can be imparted to learners. Based on these insights, the researchers proposed ways to integrate Ubrug Banten into ethnic-based learning to optimize learners' development. This integration can be achieved through role-playing methods and incorporating 21st-century competencies.